JENIS TUMBUHAN DAN KONDISI HUTAN MANGROVE DI NUSA LEMBONGAN DAN NUSA CENINGAN, KECAMATAN NUSA PENIDA, KABUPATEN KLUNGKUNG - Sugi Wahyuni, I G. A.; Parwanayoni, N. M. Susun; Wiryatno, Joko (Bumi Lestari Journal of Environment, 2012)
This research was undertaken in Nusa Lembongan and Nusa Ceningan, District of Nusa Penida, Klungkung Regency, between 2005-2006. This reserach was aimed to find out the size of area and the status of mangrove forest, kind of species, as well as problems faced by the forest related to its conservation status. From this research it was revealed that the size of the area where the mangrove available in Nusa Lembongan was around 212 ha, and there was also mangrove forest in Nusa Ceningan about 15 ha. There were 13 species of flora available on mangrove ecosystem which were classified as true mangroves, while 9 kinds were asociated mangroves. From the field observation it was revealed that there is a possible threat to the mangrove forest if there is no good management strategy. Some activities which were available on the mangrove forest that were potentially provided impacts to sustainability of the forest, such as the use for anchoring boats and mangrove tour activities.
Keywords: mangrove, sustainability, flora, manggrove zone